Sequentiality Versus Simultaneity: Interrelated Factor Demand - Asphjell, Magne K.; Letterie, Wilko; Nilsen, Øivind A.; Pfann, Gerard A. (The Review of Economics and Statistics, 2014)
Firms may adjust capital and labor sequentially or simultaneously. In this paper, we develop a structural model of interrelated factor demand subject to nonconvex adjustment costs and estimated by simulated method of moments. Based on Norwegian manufacturing industry plant-level data, parameter estimates reveal cost advantages for adjusting capital and making net changes in labor simultaneously. Factor demand models with fully specified interrelated adjustment costs structures perform best to describe the dynamic panel data.